Helium on planar and nanostructured alkali-metal surfaces - Ancilotto, F. (2009)
We investigate the effects (on the wetting characteristics of helium below 3 K) of tailoring an alkali-metal surface by incorporating a regular array of nanoscopic indentations. We establish the prewetting line of helium on semi-infinite planar Cs up to 3 K in the frame of a finite-range temperature-dependent density-functional theory, and examine the modifications introduced in the isotherms when the substrate is covered with a periodic lattice of parabolic cavities. We show that, both for the planar and nanostructured surfaces, the unstable regions of the isotherms are stabilized by nucleation of drops and/or bubbles. Results corresponding to nonwettable Cs surfaces are compared with those obtained both for planar and nanopatterned Na substrates, where wetting at zero temperature is instead expected to occur, for a planar surface, preceded by a first-order prewetting transition. © 2009 The American Physical Society.